(untitled) (Global Journal of Human-Social Science, 2019)
Previous studies conceive of La Plaza as a simple geographical space that organized crime groups dispute to obtain a monopoly on the market for illegal substances This interpretation is reduced It is necessary to conceive of La Plaza as a social actor who from the implementation of the power surveillance and punishment control devices Foucault 2003 determines the framework of social life constructs subjectivity and modifies the behavior of actors that interact directly with it ie public security agents rival groups subjects that integrate it and the general population Faced with a state of absent welfare which no longer creates certainty of incorporation and social mobility coupled with the sumptuary consumption promoted by the cultural entertainment industry La Plaza transcends its institutional capacity Lewkowicz 2006 Castoriadis 2007 for a side offer sense of life on the other by fear of being violated disrupts the biographical trajectories of the population in general